Research of the concept of monitoring the activity of the construction company - Nazarov, E. (Ways to Improve Construction Efficiency, 2020)
The role of monitoring in the current control system is substantiated. At the present stage, domestic construction companies operate in very harsh conditions. Environmental factors (for example, increased levels of competitive activity in the market, inflation, currency exchange rates, etc.) can be both stimulants and where stimuli change the level of competitive position of an enterprise in the market. Having analyzed the existing views on the methodological approach of monitoring the activity of the enterprise, we can conclude that today there is no single methodology for monitoring the activity of the enterprise. The systems of indicators offered by scientists are imperfect because they do not take into account all aspects of financial and economic monitoring of the enterprise. Therefore, it is important for the enterprise to carry out monitoring, which should quickly identify changes in the environment and provide information about them in order to promptly correct the activity of the enterprise, as well as the need to formulate a clear monitoring model that specifies the objects of monitoring within the areas of enterprise functioning, namely: spheres of logistical support, production, financial, marketing, product spheres. The essence and tasks of monitoring are considered as a system of continuous observation of a number of key indicators that characterize the state of an object and its importance in forming the system of management decision-making at the enterprise. The problems of construction enterprises, which characterize the features of the process in modern conditions, are investigated. The main stages of monitoring organization at construction enterprises are determined. The criteria for monitoring by areas of operation are also highlighted. Properly organized system of financial and economic monitoring contributes to the adaptation of the company to changes in the internal and external environment, allows to increase the validity of management decisions by timely development of measures to eliminate the impact of negative factors on the financial and economic performance of the enterprise. Thus, the advantages that an enterprise acquires when organizing the monitoring of economic activity are presented.